An Analysis of the Impact of Population and Poverty on Economic Growth in Kerinci Regency - Rosi, Adek Irma (The Future of Education Journal, 2025)
Economic growth is a crucial indicator reflecting the success of regional development. This study aims to analyze the influence of population and poverty on economic growth in Kerinci Regency. This research is quantitative. The data used are secondary data, including population, poverty rates, and economic growth for Kerinci Regency during the 2015-2024 period, obtained from the Central Statistics Agency (BPS) and related agencies. Data analysis was conducted using multiple linear regression to determine the effect of the independent variables (population and poverty) on the dependent variable (economic growth). The results indicate a significant simultaneous effect between population and poverty on economic growth. The simultaneous effect of population and poverty on economic growth in Kerinci Regency is 88%, with the remaining 12% being influenced by other factors outside this study.